J/ψ production at midrapidity in p-Pb collisions at √sNN = 8.16 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (Springer Science and Business Media Deutschland GmbH, 2023)
The production of inclusive, prompt and non-prompt J/ψ was studied for the first time at midrapidity (−1.37 < ycms < 0.43) in p-Pb collisions at √sNN = 8.16 TeV with the ALICE detector at the LHC. The inclusive J/ψ mesons were reconstructed in the dielectron decay channel in the transverse momentum (pT) interval 0 < pT < 14 GeV/c and the prompt and non-prompt contributions were separated on a statistical basis for pT > 2 GeV/c. The study of the J/ψ mesons in the dielectron channel used for the first time in ALICE online single-electron triggers from the Transition Radiation Detector, providing a data sample corresponding to an integrated luminosity of 689 ± 13 µb−1. The proton-proton reference cross section for inclusive J/ψ was obtained based on interpolations of measured data at different centre-of-mass energies and a universal function describing the pT-differential J/ψ production cross sections. The pT-differential nuclear modification factors RpPb of inclusive, prompt, and non-prompt J/ψ are consistent with unity and described by theoretical models implementing only nuclear shadowing.
Keywords: Hadron-Hadron Scattering, Quarkonium; https://purl.org/pe-repo/ocde/ford#1.03.03